2018
DOI: 10.1007/s00246-018-1853-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Low-Dose Amiodarone Therapy for Tachyarrhythmia in Congenital Heart Disease

Abstract: Amiodarone (AMD) is a class III anti-arrhythmic drug that is highly effective for tachyarrhythmia treatment. AMD is widely used in adults with congenital heart disease (CHD); however, higher doses of AMD (> 200 mg/day) can cause various non-cardiac side effects. The purpose of this study was to assess the efficacy, safety, and adverse events of low-dose AMD (≤ 200 mg/day) for tachyarrhythmia in patients with CHD. We retrospectively studied 80 patients with CHD and tachyarrhythmia who received oral low-dose AMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Nineteen studies did not report outcomes of interest and were excluded. Thus, the final analysis included 10 observational studies-specifically, seven retrospective cohort studies [7][8][9][10][11][12][13] and three prospective cohort studies 4,14,15 -involving a total of 901 patients. The literature retrieval, review, and selection processes are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies did not report outcomes of interest and were excluded. Thus, the final analysis included 10 observational studies-specifically, seven retrospective cohort studies [7][8][9][10][11][12][13] and three prospective cohort studies 4,14,15 -involving a total of 901 patients. The literature retrieval, review, and selection processes are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown an increased incidence (up to 30%) of amiodarone-induced thyrotoxicosis in adults with CHD, with patients with a Fontan circulation being at highest risk [198,199]. However, other studies have found amiodarone to be safe at lower doses and if patients with low body mass index are excluded [200,201].…”
Section: Medical Therapymentioning
confidence: 99%
“…Adjunctive medications with known benefits, such as arrhythmia prevention [ 121 ], symptom reduction [ 122 ], mitigation of neurohormonal activation [ 50 ], and closure of the patent ductus arteriosus in treating CHDs [ 123 ], are reported for angiotensin receptor-neprilysin inhibitors (ARNIs) [ 103 , 124 ], antiarrhythmics [ 125 ], digoxin [ 126 ], and non-steroidal anti-inflammatory drugs (NSAIDs) [ 127 ].…”
Section: Drugs For Chd Treatmentmentioning
confidence: 99%